2021
DOI: 10.5194/acp-21-7545-2021
|View full text |Cite
|
Sign up to set email alerts
|

Shape dependence of snow crystal fall speed

Abstract: Abstract. Improved snowfall predictions require accurate knowledge of the properties of ice crystals and snow particles, such as their size, cross-sectional area, shape, and fall speed. The fall speed of ice particles is a critical parameter for the representation of ice clouds and snow in atmospheric numerical models, as it determines the rate of removal of ice from the modelled clouds. Fall speed is also required for snowfall predictions alongside other properties such as ice particle size, cross-sectional a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…Then, the m vs. D max , m vs. A, and v vs. m relationships are fitted to the median masses vs. median maximum dimensions, median masses vs. median cross-sectional areas, and median fall speeds vs. median masses, respectively. Vázquez-Martín et al (2021) found that about 40 particles in a shape group (currently the lowest number in our dataset is 37) is the limit where binning can still be used. The advantages of binning become prominent only at larger numbers of particles.…”
Section: Fitting Relationships To Datamentioning
confidence: 90%
See 4 more Smart Citations
“…Then, the m vs. D max , m vs. A, and v vs. m relationships are fitted to the median masses vs. median maximum dimensions, median masses vs. median cross-sectional areas, and median fall speeds vs. median masses, respectively. Vázquez-Martín et al (2021) found that about 40 particles in a shape group (currently the lowest number in our dataset is 37) is the limit where binning can still be used. The advantages of binning become prominent only at larger numbers of particles.…”
Section: Fitting Relationships To Datamentioning
confidence: 90%
“…The dataset consists of 2461 high-resolution dual images of falling natural snow crystals and other hydrometeors. The same dataset has been used in Vázquez-Martín et al (2021). The data have been collected using D-ICI, the ground-based in situ instrument described in Kuhn and Vázquez-Martín (2020), at a site in Kiruna, Sweden (67.83 • N, 20.41 • E), described in Vázquez-Martín et al (2020) during multiple snowfall seasons, the winters of 2014/15 to 2018/19.…”
Section: Datasetmentioning
confidence: 99%
See 3 more Smart Citations